Improving Students’ Speaking Skill Through Audio Visual Media At 4 th Grade of Labschool Elementary School East Jakarta - . Herlina (International Conference on Education and Language (ICEL), 2014)
This research aims at helping students to improve their speaking skill by using audio visual media. The subject of the research was fourth grade students of Labschool Elementary School. This research was conducted at Labschool Elementary School Rawamangun  East Jakarta at 2nd semester of 2013 with 28 students as participants. The method conducted in this research was classroom action research by Kemmis and McTaggart. The research was carried out in two cycles. The research method is conducted through planning stages, class action/implementation, observation, and evaluation. All of these actions conducted  by the teacher through teaching in the class using audio visual media. The data was collected by using test instruments, non-test, and field notes. The result of students speaking skill evaluation on first cycle was 64,28% and 85,71%for the second cycle. It proves that the outcome of students speaking skill was improve into 21,42% due to the effectiveness of learning process through audio visual media. The conclusion of the research is by using audio visual media to learn english, the students’ speaking skill at fourth grade of Labschool Elementary School Elementary School Rawamangun East Jakarta will improve significantly.